VAV 및 VWV시스템 적용에 따른 업무용 건축물의 에너지저감에 관한 연구 - 송지용; 홍원화; 김지연; 박효순; Song, Ji-Yong; Hong, Won-Hwa; Kim, Ji-Yeon; Park, Hyo-Soon (生態環境建築, 2013)
Building Energy Efficiency Rating system was enforced in 2001 to enhance spreading high-energy performance and saving buildings. It was only for the new apartments, but expanded to new office buildings in 2010, and moreover, government offices require 1st grade of Building Energy Efficiency Rating system. Green Building Act, which is established to reduce the emissivity of carbon dioxide by reducing building energy consumption, will be enforced in 2013, and new apartments and office buildings will be subjected to it. Henceforward, it will extend to other types of buildings and will be phased in. In general, pumps and fans consume approximately half of the air-conditioning energy consumption, and about a quarter of the total building energy consumption when office buildings have total floor area of more than 10000 square meters. This study analyzed the energy demand when applying VAV(Variable Air Volume) and VWV(Variable Water Volume) System to reduce energy returns of the pumps and the fans by ECO2, which is a computer simulation program used for Building Energy Efficiency Rating system.